Towards a unity of ecology and ordinary ethics : on everyday life and aspirations to live sustainably in a permaculture community - Roux, Tarien (Social Anthropology, 2015)
Conventional agriculture is a significant contributor to climate change, itself a socially driven ecological phenomenon. Until recently, however, social science has only just begun to engage intensely with the relationship between agriculture and global climate change and also on developing a viable sustainable response thereto. Following, this dissertation is premised on the understanding that sustainability requires an integration of human settlement patterns and sustainable agricultural practices. The dissertation uses ethnographic data about a permaculture community that practices such an integrated existence as a demonstration of permaculture's primary ethic to take responsibility for one's own existence. By asking what it means to say that the residents produce their own lives, the dissertation traces the theoretical and environmental context and structures that shape and are shaped by the intentional community that has formalised itself as a nonprofit organisation with an educational mandate. It explores how these two meet and provides a demonstration of the residents' community-based lifestyle as infused with aspirations to sustainability. This dissertation argues that the residents integrated human settlement patterns with sustainable agriculture through internalising design and building costs, and decentralising agricultural energetic inputs and outputs; and that these activities inserted an ethic of care at the core of the labour activities that constituted the everyday lives of residents. Further, that everyday life there exhibited an aspiration to living sustainably as the grassroots implementation of permaculture's pedagogical ethos of living an integrated existence as a positive response to climate change.